1996
DOI: 10.1007/bf01209031
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy after hyperbaric oxygenation for malignant gliomas: a pilot study

Abstract: The results of radiotherapy combined with hyperbaric oxygen in 9 patients with malignant glioma were compared with those of radiotherapy without hyperbaric O2 in 12 patients. This is the first report of a pilot study of irradiation immediately after exposure to hyperbaric O2 in humans. All patients receiving this treatment showed more than 50% regression of the tumor, and in 4 of them, the tumors disappeared completely. Only 4 out of 12 patients without hyperbaric O2 showed decreases in tumor size, and all 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…In addition, the dose correction of radiation absorbed in the chamber wall is complex. But our new protocol that involved irradiation immediately after HBO exposure was simple and safe compared to radiotherapy during HBO exposure (Kohshi et al, 1996). The results of the present non-invasive study supported the theory that elevated MR signal intensity indicates tissue PO 2 in the tumours was maintained for substantial periods after decompression.…”
Section: Clinical Application Of Hbosupporting
confidence: 78%
See 1 more Smart Citation
“…In addition, the dose correction of radiation absorbed in the chamber wall is complex. But our new protocol that involved irradiation immediately after HBO exposure was simple and safe compared to radiotherapy during HBO exposure (Kohshi et al, 1996). The results of the present non-invasive study supported the theory that elevated MR signal intensity indicates tissue PO 2 in the tumours was maintained for substantial periods after decompression.…”
Section: Clinical Application Of Hbosupporting
confidence: 78%
“…As a result, HBO has not been routinely adopted with radiotherapy to treat patients with cancer. We irradiated human malignant gliomas 15 min after HBO exposure based on the hypothesis that elevated partial oxygen tension (PO 2 ) in the tumours was maintained for substantial periods after decompression (Kohshi et al, 1996). Using invasive measurements, it was reported that tissue PO 2 increased slowly during HBO exposure and that the decline in PO 2 after HBO was slower in subcutaneous tissues than in muscles (Wells et al, 1977), but no study on PO 2 change of tumours after HBO has been reported.…”
mentioning
confidence: 99%
“…Six of these papers described single-arm studies in which all patients received, as the standard of care, HBO followed by RT 14,[21][22][23][24][25] . The other two articles described double-arm studies in which one patient group received RT without HBO and the other group received HBO then RT 19,26 . The six single-arm studies included a total of 203 patients; 142 of these patients had glioblastoma (WHO grade IV glioma) while the other 61 patients had anaplastic glioma (WHO grade III) ( Table 1) 14,[21][22][23][24][25] .…”
Section: Resultsmentioning
confidence: 98%
“…The two double-arm studies included a total of 24 patients who were treated with RT plus HBO and 26 patients who received only RT (Table 3) 19,26 . As in the single arm studies, all gliomas were high grade; 33 were grade IV and 17 were grade III.…”
Section: Current Medical Research and Opinion 2015mentioning
confidence: 99%
“…A number of previous studies have indicated that combining hyperbaric oxygen treatment with chemoradiotherapy may improve the prognosis for glioma patients and reduce complications (13)(14)(15)22); however, the specific mechanism by which this occurs remains unknown. A previous study proposed that hyperbaric oxygen may induce apoptosis in tumor cells and decrease the vascular density in subcutaneous …”
Section: Discussionmentioning
confidence: 99%